2013
DOI: 10.1016/j.micinf.2012.11.007
|View full text |Cite
|
Sign up to set email alerts
|

DNA vaccine encoding peptide P10 against experimental paracoccidioidomycosis induces long-term protection in presence of regulatory T cells

Abstract: Paracoccidioidomycosis is a granulomatous systemic mycosis endemic in Brazil and other Latin America countries. A DNA vaccine encoding the immunoprotective peptide 10 (P10) significantly reduced the fungal burden in mice when given prior to or after intratracheal challenge with Paracoccidioides brasiliensis. Presently, the generation/expansion of CD4+ CD44hi memory T cells as well as Foxp3+ Treg cells in mice immunized with the DNA vaccine (pcDNA3-P10) before and after infection with P. brasiliensis was invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 47 publications
(61 reference statements)
1
20
1
5
Order By: Relevance
“…However, since PCM primarily affects rural workers, the disease is associated with significant social and economic factors that mostly affect less affluent populations (Shikanai-Yasuda et al, 2006; de Amorim et al, 2013), so the development of new molecules that could work as a vaccine directed at high-risk populations could be an important step in effective prophylaxis for this disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, since PCM primarily affects rural workers, the disease is associated with significant social and economic factors that mostly affect less affluent populations (Shikanai-Yasuda et al, 2006; de Amorim et al, 2013), so the development of new molecules that could work as a vaccine directed at high-risk populations could be an important step in effective prophylaxis for this disease.…”
Section: Discussionmentioning
confidence: 99%
“…Another study investigating the role of B-1 cells in pulmonary PCM showed their deleterious effect, which was attributed to the increased migration and activation of Treg cells [107]. In contrast with those previously described deleterious effects of Treg cells, a study employing a repeated immunization with a DNA vaccine encoding the immunoprotective peptide (P10) from gp43, the main diagnostic antigen of P. brasiliensis, conferred a long-term protection to infected mice by inducing increased numbers of memory and regulatory T cells able to control the infectious process and the inflammatory tissue pathology [108].…”
Section: Regulatory T Cells In Murine Pcmmentioning
confidence: 92%
“…There are some reports describing the role of antigens inducing immune responses against P. brasiliensis such as soluble antigen, purified antigen, peptide, DNA vaccine and the use of attenuated yeast cells [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%